Importance of the inhalation device on the effect of budesonide. Issue 1 (July 1993) - Agertoft, L; Pedersen, S
Abstract : Two hundred and forty one children with chronic perennial asthma, who had been treated with budesonide via a metered dose inhaler with a spacer device (Nebuhaler), had their normal dose of budesonide reduced by 50% to determine if they had been overtreated. Within three weeks, asthma control deteriorated in 126 patients to such an extent that budesonide had to be increased to the normal dose. After stabilising their asthma, these children were enrolled in a randomised, double blind, double dummy, parallel study, performed to compare the effect of budesonide via Nebuhaler with that of half the dose of budesonide via Turbuhaler. The study started with a two week run-in during which patients were treated with their normal dose of budesonide via Nebuhaler. After run-in, 64 children were randomised to treatment with their normal budesonide treatment and the remaining 62 children to treatment with half their normal dose via Turbuhaler for nine weeks. Throughout the study, patients recorded asthma symptoms, peak flow measurements, and beta 2 agonist use in a diary. Pulmonary function tests, exercise tests, and 24 hour urine sample collections were performed at hospital visits during run-in and the study period. Apart from beta 2 agonist use, which was significantly lower for patients on Turbuhaler treatment than on Nebuhaler treatment, there were no differences between the groups in any of the parameters studied during run-in or during the study period. Furthermore, there was no trend of deterioration in asthma control when the dose of budesonide was reduced by 50% when Turbuhaler was the inhalation device. It is concluded that budesonide via Turbuhaler is more effective than via Nebuhaler in the treatment of asthma. Based on this finding, attempts should be made to reduce the dose of budesonide when patients are switched from Nebuhaler to Turbuhaler treatment.